Nos informamos con las noticias - Acuña Toro, Leyson Esly (2018)
The present learning session to which he entitled "We inform ourselves with the news" has as part of his planning the express competence "expresses his needs, interests, feelings and expressions, and listens with respect when interacting with others, shows understanding of messages simple in their native language and in Spanish”. It follows the indicator of achievement called: "explains the cause of a fact and the action of a simple structure narrative text with images."_x000D_ On the other hand it is important to remember that the aforementioned competition works with the following capabilities: Listen and understand simple messages, Tell stories (classics) fables, stories of your people and personal or related facts using simple expressions and sentences. Incorporate in their descriptions the characteristics of people, animals, places and objects of their surroundings, in order, using simple and clear expressions.